EGGS AND LARVAE OF AN ENGRAULID AND TWO CARANGIDS FROM MADRAS PLANKTON - Rao, K Satyanarayana; Girijavallabhan, K G (Indian Journal of Fisheries, 2011)
The eggs of Thrissocles mystax are colourless, roughly spherical, and have a diametervarying between 0.912 nun and 1.270 mm and coarsely segmented yolk. The newlyhatched pro-larva has thirty pre-Â«ml and ten or eleven post-anal myotomes. The threeday old post-larva has thirty pre-anal and thirteen post-anal myotomes, pectoral finsand small streak like black pigmentation on the gut.